2019
DOI: 10.4162/nrp.2019.13.4.352
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nutrition literacy on the food habits among young adults in Turkey

Abstract: BACKGROUND/OBJECTIVES Youth is the crucial stage between childhood and adulthood during which an individual acquires new behavior and practices including dietary habits, that may be influenced by his peers, social circle, nutrition knowledge level and other factors. The increase in awareness of young adults is of special importance from the perspective of health and prevention of obesity related chronic diseases. To measure the nutrition literacy level of university students using the Turkish vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 27 publications
8
63
0
7
Order By: Relevance
“…The study of Viggiano et al [ 36 ] conducted in a group of Italian children and adolescents indicated that an AFHC score obtained without any intervention was 10.9. Similarly, the study by Kalkan [ 37 ] carried out among Turkish adolescents assessing their eating habits using AFHC revealed that females obtained significantly higher scores than males (mean score: 10.37 vs 9.26, respectively), and thus inferred that women were having more health-promoting eating habits than men. Interesting findings were also observed by Koca and Arkan [ 42 ] in their study determining the dietary habits of Turkish adolescents.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The study of Viggiano et al [ 36 ] conducted in a group of Italian children and adolescents indicated that an AFHC score obtained without any intervention was 10.9. Similarly, the study by Kalkan [ 37 ] carried out among Turkish adolescents assessing their eating habits using AFHC revealed that females obtained significantly higher scores than males (mean score: 10.37 vs 9.26, respectively), and thus inferred that women were having more health-promoting eating habits than men. Interesting findings were also observed by Koca and Arkan [ 42 ] in their study determining the dietary habits of Turkish adolescents.…”
Section: Discussionmentioning
confidence: 90%
“…The questionnaire used in the study to collect information about dietary habits during the COVID-19 pandemic was AFHC, which was developed by Johnson et al [ 34 ] and validated in a group of adolescents [ 34 ]. It is a commonly applied and efficient tool that enables, the eating habits of not only adolescents [ 35 , 36 ] but also adults [ 37 ] to be determined.…”
Section: Methodsmentioning
confidence: 99%
“…NL is important for assessing changes in nutritional habits. In a study, FH have been reported to be affected by NL (51) . In our study, adolescents' ability to obtain, interpret and apply information about nutrition was found to affect healthy eating behaviours.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of foods alone does not necessarily translate into an optimal dietary intake. However, the choice of what, how, and when to eat is governed by several factors of which nutrition literacy is among the tops [4,5,6]. Studies have shown that poor dietary intake is linked with a high level of nutritional illiteracy in the population [7,8].…”
Section: Introductionmentioning
confidence: 99%